Effect of Clonidine (an Antihypertensive Drug) Treatment on Oxidative Stress Markers in the Heart of Spontaneously Hypertensive Rats - Nik Yusoff, Nik Syamimi; Mustapha, Zulkarnain; Govindasamy, Chandran; Sirajudeen, K. N. S. (Hindawi Publishing Corporation, 2013)
Hypertension is a risk factor for several cardiovascular diseases and oxidative stress suggested to be involved in the pathophysiology. Antihypertensive drug Clonidine action in ameliorating oxidative stress was not well studied. Therefore, this study investigate the effect of Clonidine on oxidative stress markers and nitric oxide (NO) in SHR and nitric oxide synthase inhibitor, N-nitro-L-arginine methyl ester (L-NAME) administered SHR. Male rats were divided into four groups [SHR, SHR+Clonidine (SHR-C), SHR+LNAME, SHR+Clonidine+L-NAME(SHRC+L-NAME)]. Rats (SHRC) were administered with Clonidine (0.5mg kg−1 day−1) from 4 weeks to 28 weeks in drinking water and L-NAME (25mg kg−1 day−1) from 16 weeks to 28 weeks to SHRC+L-NAME. Systolic blood pressure (SBP) was measured. At the end of 28 weeks, all rats were sacrificed and in their heart homogenate, oxidative stress parameters and NO was assessed. Clonidine treatment significantly enhanced the total antioxidant status (TAS) (